Seasonal Variation and Regression Prediction of Fatty Acid Compositions in Tuna Oil from Three Tuna Species (Katsuwonus pelamis, Thunnus tonggol and Euthynnus affinis) - Srichan, Rungsang; Worawattanameteekul, Wanchai; Tepwong, Pramvadee (Food and Applied Bioscience Journal, 2017)
Tuna heads, by-products from canned tuna industry, are used as raw materials for processing fish oils. Lipid composition of tuna head is a good source of beneficial fatty acids, especially Eicosapentaenoic acid (EPA) and Docosahexaenoic acid (DHA). They are the important keys of fish oil quality. The propose of this research work was aimed to determine the fatty acid composition in the heads of three different tuna species (Katsuwonus pelamis, Thunnus tonggol, and Euthynnus affinis) collected from canned tuna industry in Samut Sakhon Province, Thailand in different seasons. The results showed that high quality tuna oil processed from E. affinis sample caught between February and May had the highest contents of PUFA with 46.25% and 28.86% of DHA contents (p<0.05). The percentage of major fatty acids composition of tuna heads predicted by regression correlation from the fatty acid profiles over three different periods between 2014 to 2015 from February to May, from June to September, and from October to January were used to study seasonal variation. The spawning season of tunas (October to January) gave the lowest DHA, Omega-3 and PUFA compositions compared to the other two periods of time.